Community stoichiometry in a changing world: combined effects of warming and eutrophication on phytoplankton dynamics. Issue 6 (1st June 2014) - De Senerpont Domis, Lisette N.; Van de Waal, Dedmer B.; Helmsing, Nico R.; Van Donk, Ellen; Mooij, Wolf. M.
Abstract : The current changes in our climate will likely have far‐reaching consequences for aquatic ecosystems. These changes in the climate, however, do not act alone, and are often accompanied by additional stressors such as eutrophication. Both global warming and eutrophication have been shown to affect the timing and magnitude of phytoplankton blooms. Little is known about the combined effects of rising temperatures and eutrophication on the stoichiometry of entire phytoplankton communities. We exposed a natural phytoplankton spring community to different warming and phosphorus‐loading scenarios using a full‐factorial design. Our results demonstrate that rising temperatures promote the growth rate of an entire phytoplankton community. Furthermore, both rising temperatures and phosphorus loading stimulated the maximum biomass built up by the phytoplankton community. Rising temperatures led to higher carbon : nutrient stoichiometry of the phytoplankton community under phosphorus‐limited conditions. Such a shift towards higher carbon : nutrient ratios, in combination with a higher biomass buildup, suggests a temperature‐driven increase in nutrient use efficiency, the phytoplankton community. Importantly, with higher carbon : nutrient stoichiometry, phytoplankton is generally of poorer nutritional value for zooplankton. Thus, although warming may result in higher phytoplankton biomass, this may be accompanied by a stoichiometric mismatch between phytoplankton and their grazers, with possible consequences for the entire aquatic food web.